The utility of self-reported psychopathic traits in predicting recidivism among a sample of incarcerated female youths. (July 2020) - Pechorro, Pedro; Ray, James V.; Alberto, Isabel; Simões, Mário R.
Abstract: Only a few studies have prospectively examined the utility of self-reported measures of psychopathic traits in predicting criminal behavior among forensic samples of female youth offenders. The main aim of this study is to compare the utility of two self-report measures of psychopathic-like traits in predicting criminal recidivism among a sample of incarcerated female youths. Participants ( N  = 76) from the three nation-wide Portuguese juvenile detention centers that admit female youths were followed over two years and prospectively classified as recidivists versus non-recidivists. Logistic regression models controlling for crime frequency and ethnicity revealed that neither the Antisocial Process Screening Device – Self-Report (APSD-SR) nor the Youth Psychopathic Traits Inventory (YPI) and their respective dimensions significantly predicted one- and two-year general recidivism and violent recidivism. Findings mostly suggest there are clear limitations in terms of the incremental utility of self-report measures of psychopathic traits in predicting criminal recidivism among incarcerated female juveniles.